Effect of the BOPPPS model combined with case-based learning versus lecture-based learning on ophthalmology education for five-year paediatric undergraduates in Southwest China - Chen, Lin; Tang, Xiao-Jiao; Chen, Xin-Ke; Ke, Ning; Liu, Qin (BMC medical education, 2022)
Background To investigate the effect of the bridge-in, objective, preassessment, participatory learning, post assessment, and summary (BOPPPS) model combined with case-based learning (CBL) on ophthalmology teaching for five-year paediatric undergraduates. Methods The effects of the BOPPPS model combined with CBL (BOPPPS-CBL) and traditional lecture-based learning (LBL) on ophthalmology teaching were compared among students in a five-year programme. The questionnaire surveys of the students were collected and statistically analysed after the class. The final examination scores, including on elementary knowledge and case analysis, in the two groups were analysed. Results There were no statistically significant differences between the teachers and students in the baseline data. More students agreed that the BOPPPS-CBL model helped develop their problem-solving skills, analytical skills and motivation for learning better than the LBL model. There was no significant difference in learning pressure between the two groups. The final examination scores of the BOPPPS-CBL group were significantly higher than those of the LBL group. The overall course satisfaction of the BOPPPS-CBL group was obviously higher than that of the LBL group. Conclusions The BOPPPS-CBL model is an effective ophthalmology teaching method for five-year paediatric undergraduates.